Technology and persistence in global software piracy - Simplice Asongu; Christelle Meniago (African Governance and Development Institute (AGDI), 2018)
This study examines the persistence of software piracy with internet penetration vis-à-vis of PC users, conditional on Intellectual Property Rights (IPRs) institutions. The empirical evidence is based on a panel of 99 countries for the period 1994-2010 and the Generalised Method of Moments. The main finding is that, compared to internet penetration, PC usage is more responsible for the persistence of global software piracy. Knowing how technology affects the persistence of piracy is important because it enables more targeted policy initiatives. We show that the sensitivity of software piracy to IPRs mechanisms is contingent on the specific technology channels through which the pirated software is consumed.
Keywords: F42; K42; O34; O38; O57; 330; Piracy; Business Software; Software piracy; Intellectual Property Rights